Chapter Impact of cliff erosion on marine sediment composition - indication of local coastline evolution (Vrgada Island, Croatia) - Furcic, Nina (Proceedings e report, 2020)
Erosive coastal cliffs formed in soft-rocks sediments along the generally carbonaceous Eastern Adriatic are a rare feature. The one from the Vrgada Island gave rise to the idea that local seabed surface sediment may reflect the composition of the cliff sediment. First results of sedimentological analyses showed that sediment samples collected on both sides of the cliff contain material eroded mostly from the eastern side of the cliff. Subsequent longshore drift caused by dominant waves likely sort fallen material, transporting its finer fractions to the northern side and further into the sea.